KOHESI GRAMATIKAL DAN LEKSIKAL DALAM PANTUN BANGKA (Gramatical and Lexical Cohesion in Bangka Pantun) - Hidayatul Astar (﻿Kantor Bahasa Provinsi Bangka Belitung, 2019)
Berpantun merupakan cara berkomunikasi yang khas dalam masyarakat Melayu. Ada sampiran dan ada isi. Pada umumnya, antarsampiran dan antarisi memiliki hubungan atau kohesif yang ditandai oleh pemarkah kohesi. Dalam artikel ini akan dibahas perangkat kohesi dan satuan bahasa yang dihubungkannya. Alat analisis digunakan adalah takosomi kohesi yang dikemukakan Hallliday dan Hasan (76). Hasil kajian terhadap pantun, khususnya Pantun Bangka, menunjukkan bahwa dua jenis kohesi, yaitu kohesi gramatikal dan kohesi leksikal, digunakan. Kohesi antarsampiran dan antar isi terbagi dua, yaitu kohesi intrakalimat dan kohesi antarkalimat. Data kuantititaf menunjukkan bahwa antarsampiran pantun Bangka lebih banyak berkohesi antarkalimat daripada berkohesi intraklimat. Dari 202 pasangan sampiran 76 atau 37, 62% berkohesi intrakalimat, 103 atau 50,99% berkohesi antarkalimat, dan 23 atau 11,39% tidak berkohesi. Kohesi antarkalimat ditandai oleh konjungtor, pengulangan kata atau frasa, pengacuan, dan hiponimi. Sementara itu, kohesi intrakalimat ditandai oleh konjungtor penanda kalimat majemuk yang menyatakan hubungan tertentu. Jika kohesi antarsampiran lebih banyak berkohesi antarkalimat, kohesi antarisi sebaliknya, yaitu lebih banyak berkohesi intrakalimat daripada antarkalimat. Dari 202 pasangan isi 116 atau 57, 43% berkohesi intrakalimat, 74 atau 36,63% berkohesi antarkalimat, dan 12 atau 5,94% tidak berkohesi. Data kuantitaif ini menujukkan bahwa isi pantun lebih mengutamakan kalimat yang mudah dipahami. Oleh karena itu, hubungan intrakalimat lebih banyak daripada hubungan antarkalimat. Seperti dalam sampiran, kohesi intrakalimat antarisi ditandai oleh konjungtor kalimat majemuk dan kohesi antarkalimat oleh konjungtor antarkalimat, pengulangan kata atau frasa, pengacuan, dan hiponimi. Talking through pantun is a typical way of communicating in Malay. There is sampiran and there is content. In general between one another sampiran and another content have a relationship or cohesive characterized by cohesion device. In this article we will discuss the cohesion device and the unit of language it connects. As an analytical tool used cohesion takosomy presented.The cohesion tool can be explicit and can olso implicit. The results of the study of the pantun especially the Bangka’Pantun show that there are two types of cohesion, namely grammatical cohesion and lexical cohesion. Quantitative data shows that in the Bangka's pantun between one sampiran and another has more cohesion between between one sentence and the another than the cohesion in the sentence. Of the 202 couples sampiran 76 or 37, 62% use in cohesion in the sentence, 103 or 50.99% use in the cohesion between one sentence and other, and 23 or 11.39% no cohesion. Cohesion between one and other sentence is characterized by conjunctors, repetition of words or phrases, reference, and hyponymy. Meanwhile, cohesion in the sentence is characterized by conjunctors of compound sentences that express certain relationshipsIf the cohesion between one sampiran and other is more many the have cohesion between one sentence and other, the cohesion between one contens and other is the opposite, is more many have the cohesion ini one sentence. Of the 202 pairs of contents 116 or 57, 43% had the cohesion in the sentence, 74 or 36.63% had the cohesion one sentence and other, and 12 or 5.94% had no cohesion. This quantitative data shows that the contents of the pantun give priority to easily understood sentences. Therefore, The cohesion in the sentence are more than the cohesion between one and another sentence. As on the sampiran, the cohesion one conten and other is characterized by conjunctors of compound sentences and the cohesion between one sentence and other also characterized by inter-sentence conjunctors, repetition of words or phrases, reference, and hyponymy.